Amaurosis fugax and carotid artery disease: indications for angiography. Issue 6084 (13th August 1977) - Wilson, L A; Russell, R W
Abstract : A prospective study of 80 patients presenting with amaurosis fugax was performed in an attempt to relate clinical features to angiographic findings in the internal carotid artery. Carotid bruit, transient cerebral ischaemic attacks, hypertension, and claudication were associated with a high prevalence of angiographic abnormality. Every patient who showed all these features had an operable lesion, as did 88% of those who had three features. In patients over 50 years of age carotid stenosis and atheromatous ulceration were occasionally found in the absence of bruit and transient cerebral ischaemia, but only one patient aged under 50 had an operable lesion and no associated features. Clinical features were therefore valuable in predicting the outcome of angiography, but it seems prudent to restrict angiography to patients aged over 50, who are most likely to benefit from surgery on the carotid artery.